(untitled) (UNED Research Journal, 2019)
Introduction: The Human-Serpent conflict in Costa Rica seems to be defined by fear. However, several studies suggest that perception and knowledge about snakes could be more positive in an urban population with a higher educational level. Objective: To evaluate the perception and knowledge about snakes among the staff of a Costa Rican public university. Methods: I designed a survey of 13 questions, some aimed at assessing perception and others aimed at evaluating knowledge. Results: I applied the survey to 340 employees, 95% have university-level studies and live within the Greater Metropolitan Area (GAM); 40% are afraid of snakes. Women feel more fear and dislike than men. Most underestimate or ignore the overall number of snake species, overestimate or ignore the number of dangerous snakes and underestimate the maximum size of a snake in Costa Rica; 73% mentioned more poisonous species than non-poisonous species. The most mentioned snakes were boa, coral, fer-de-lance, pit viper and rattlesnake. Conclusions: Despite their high educational level, these university staff members know little about snakes and would benefit from environmental education about them.